Optimization design of top beam energy absorbing member of corrugated hydraulic support with three kinds of sandwich structures based on adaptive response surface method - Zuen Shang; Qian Liu; Jiyang Meng; Peng Yang; Xisheng Yu (PLoS ONE, 2025)
To enhance the energy absorption performance of support systems in response to the frequent rockburst issues arising from deep coal mining, a new energy-absorbing component with a corrugated core structure is proposed for use in hydraulic support beams. The study explores three core structures: triangular, trapezoidal, and sine. Three structures were designed and analyzed based on a mechanical model, and simulations were conducted using ANSYS software. The study investigates the variations in support reaction force and displacement, energy absorption and displacement, as well as buckling deformation, with a detailed analysis of the simulation results. Using the Adaptive Response Surface Method, structural parameter optimization was carried out with DESIGN EXPERT software for all three core structures. After obtaining the optimal configurations, experimental tests were conducted to verify the feasibility of these new structures as energy-absorbing components for hydraulic supports. The findings suggest that the optimal angle for the triangular corrugated unit is 30° with a thickness of 2.9mm. The trapezoidal corrugated unit exhibits optimal performance at a vertical angle of 34° and a thickness of 4.2mm. With regard to the quasi-sinusoidal corrugated unit, the optimal angle is 32° with a thickness of 3.2mm. Furthermore, in single-layer structures, the sinusoidal corrugated core structure exhibits the best performance in terms of energy absorption and displacement. The introduction of corrugated energy-absorbing components opens new avenues for structural innovation and performance optimization, offering valuable insights for designing anti-impact energy-absorbing structures.